2012
DOI: 10.1021/ja303895k
|View full text |Cite
|
Sign up to set email alerts
|

A Solvatochromic Model Calibrates Nitriles’ Vibrational Frequencies to Electrostatic Fields

Abstract: Electrostatic interactions provide a primary connection between a protein’s three-dimensional structure and its function. Infrared (IR) probes are useful because vibrational frequencies of certain chemical groups, such as nitriles, are linearly sensitive to local electrostatic field, and can serve as a molecular electric field meter. IR spectroscopy has been used to study electrostatic changes or fluctuations in proteins, but measured peak frequencies have not been previously mapped to total electric fields, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
199
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(221 citation statements)
references
References 29 publications
(110 reference statements)
18
199
0
Order By: Relevance
“…[21][22][23][24][25][26][27][28] The CN and N 3 probes have the advantage of being strong chromophores; however, unlike CÀD labels, CN and N 3 substituents are extrinsic probes that may introduce interactions that are not present in the native protein, and sensitivity to these artificial interactions may desensitize them to their native protein environment. Indeed, previous studies have indicated that both probes are predominantly sensitive to hydrogen bonding, [5,[29][30][31][32][33][34] interactions introduced by the probes themselves. Moreover, as extrinsic probes they might perturb the protein, a possibility exacerbated by the size of the N 3 group and by the H-bonding propensity of both CN and N 3 groups.…”
mentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28] The CN and N 3 probes have the advantage of being strong chromophores; however, unlike CÀD labels, CN and N 3 substituents are extrinsic probes that may introduce interactions that are not present in the native protein, and sensitivity to these artificial interactions may desensitize them to their native protein environment. Indeed, previous studies have indicated that both probes are predominantly sensitive to hydrogen bonding, [5,[29][30][31][32][33][34] interactions introduced by the probes themselves. Moreover, as extrinsic probes they might perturb the protein, a possibility exacerbated by the size of the N 3 group and by the H-bonding propensity of both CN and N 3 groups.…”
mentioning
confidence: 99%
“…9 The results herein suggest that these effects are readily accommodated by augmenting experimental spectroscopy with electronic structure calculations, thereby affording a means to rationalize any deviation from purely electrostatic contributions. Coupled with Kubo-Anderson lineshape analysis this tool becomes even more versatile, facilitating exploration of the vibrational probe's solvation shell.…”
Section: Discussionmentioning
confidence: 86%
“…Thus, while the calculated shifts are not identical to the experimental shifts, the use of reference data establish a correlation can provide a quantitative conversion factor. While prior studies avoided hydrogen bonding solvents due to difficulties in interpretation, 9 these concerns may be mitigated when theoretical calculations are used to augment experimental investigations. As a final note, the scatter and deviation from a linear dependence of the solvatochromic shift on the Onsager reaction field may be attributed, in part, to the crude nature of the Onsager approximation.…”
Section: A Solvatochromic Shiftsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously used nitrile probes for proteins include CN-labelled phenylalanine 289–291 and the nitrile-containing IDD type inhibitor for human aldose reductase 278,292 . Benzonitrile (PhCN) is another potentially useful probe to determine the local electrostatic environment as it fulfills three important criteria: the -CN stretching mode at 2200 cm – 1 (a) absorbs in a frequency range (i.e., between 1800 cm – 1 and 2800 cm – 1 ) in which proteins containing only naturally occurring amino acids have no vibrational spectral response (except for the -SH group in cysteine), (b) is to a good approximation a local mode (i.e., uncoupled from other framework modes), and (c) the dipole moment of PhCN is to a large extent that of the nitrile group itself.…”
Section: Applicationsmentioning
confidence: 99%